2007
DOI: 10.1055/s-2007-985860
|View full text |Cite
|
Sign up to set email alerts
|

A New Full-Endoscopic Technique for Cervical Posterior Foraminotomy in the Treatment of Lateral Disc Herniations Using 6.9-mm Endoscopes: Prospective 2-Year Results of 87 Patients

Abstract: Anterior cervical decompression and fusion (ACDF) is the standard procedure for operation of cervical disc herniations with radicular arm pain. Mobility-preserving posterior foraminotomy is the most common alternative in the case of a lateral localization of the pathology. Despite good clinical results, problems may arise due to traumatization of the access. Endoscopic techniques are considered standard in many areas, since they may offer advantages in surgical technique and rehabilitation. These days, all dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
140
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(160 citation statements)
references
References 18 publications
(21 reference statements)
8
140
0
Order By: Relevance
“…Also the route of access in the innervation area of the dorsal branch of the spinal nerves can have a negative influence on the stabilizing and coordination system [62,63]. For this reason, attempts are made even in the primary operation, and also in revisions, to work with tissue-sparing techniques [64,65] Furthermore, technical advances have been made in the primary operation of disc herniations which enable a full-endoscopic technique and provides the advantages of a truly minimally invasive procedure [64,[66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…Also the route of access in the innervation area of the dorsal branch of the spinal nerves can have a negative influence on the stabilizing and coordination system [62,63]. For this reason, attempts are made even in the primary operation, and also in revisions, to work with tissue-sparing techniques [64,65] Furthermore, technical advances have been made in the primary operation of disc herniations which enable a full-endoscopic technique and provides the advantages of a truly minimally invasive procedure [64,[66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the disadvantage of extended surgical approach remains. To avoid the invasiveness of the above-mentioned approach different tubular or complete endoscopic procedures to the cervical spine have been introduced [3,12,15,19]. Cervical disc disease is the leading indication for endoscopic foraminotomy according to literature.…”
Section: Discussionmentioning
confidence: 99%
“…The use of full-endoscopic posterior cervical foraminotomy (FPCF) to treat lateral disc herniation was first reported by Ruetten et al [17,18] in 2007. They concluded that FPCF is a sufficient and safe supplement and alternative to conventional procedures.…”
Section: -16]mentioning
confidence: 99%
“…FPCF was performed according to the method of Ruetten et al [17] The patient was placed in the prone position under general anesthesia. In patients with pathology on the left side of C5/6, a skin incision was made under fluoroscopy at the intersection of a line at the C5/6 disc level [ Figure 2A] and a line at the medial edge of the facet joint on the left side [ Figure 2B].…”
Section: Fpcf Surgical Techniquementioning
confidence: 99%